Entre liberdades e (in)subordinações: experiências de cicloentregadoras das cidades de Belo Horizonte e São Paulo - Luiza Fleury de Freitas (2023)
Female cyclodelivery workers are located at the intersection between bicycle use in urban mobility, gender relations and the delivery activity. On one hand, these women are inserted in an urban structure planned from the privilege of automobile circulation, which controls and restricts the uses and modes of transport. On the other hand, they are subject to power relations between genders, which determine the spaces they can access and the activities they can perform. Finally, they are subordinated to the masculinization of delivery work, which standardizes the bodies that may or may not perform the function. In this context, this research has the general objective of understanding the influence of the power relations experienced in these three areas on the cycledelivery work carried out by women, based on the investigation of experiences of female cycledeliveries in the cities of Belo Horizonte and São Paulo. In addition, the research sought to identify the factors that motivate these women to make deliveries, even in the face of adversity, and the challenges and potential of this work as an instrument of liberation and emancipation. For that, we used the content analysis of in-depth interviews carried out with fourteen active female bike couriers, or who have already exercised the activity. As a result, the relevance of the power relations to which cycle delivery companies are subjected was observed, influencing, in particular, the perceptions of safety in the development of the activity. The results also showed the potential of friendships for the inclusion of these women in work and their permanence. Additionally, the complexity of analyzing the potential of cyclelogistics for the physical and mental health of couriers was observed, due to the long journeys and distances covered on a daily basis. Finally, the interviews also highlighted the provisional and complementary aspect associated with the cycledelivery activity. Despite this, the transforming potential of the activity was also demonstrated, providing an experience of great value in terms of empowerment, freedom, autonomy, and resilience.